Photonic engineering of terahertz quantum cascade lasers - Liang, Guozhen (2015)
The terahertz (THz) frequency range, lying between microwave and mid-infrared frequencies (~0.3 THz to 10 THz), remains one of the least developed regions in the electromagnetic spectrum. THz radiation has, however, proven potential widespread and important applications in, for example, spectroscopy, heterodyne detection, imaging and communications. In many of these applications, high power coherent THz sources with low beam divergence, single-mode operation, tunable intensity and controllable polarization are highly desirable. Therefore, much effort has been placed on the development of new and appropriate THz sources, and in particular with a focus on the development of electrically pumped, semiconductor-based light sources that can be mass produced. A breakthrough occurred in 2002, when the first THz quantum cascade lasers (QCLs) was demonstrated. QCLs are semiconductor lasers comprising multiple strongly coupled quantum wells, exploiting electron transitions between subbands of the conduction band. By adjusting the widths of the quantum wells/barriers, the emission frequency and performance of the laser can be tailored, adding additional flexibility in the laser design. Without the assistance of an external magnetic field, THz QCLs have covered the frequency range from 1.2 to 5 THz. With respect to the optical power, THz QCLs can provide over 1W peak power in pulse mode, and 130 mW in continuous-wave (CW), at 10 K heatsink temperature, in devices using a single-plasmon waveguide. Although relatively good performance of THz QCLs has been achieved, there is still sufficient room to further improve the performance of THz QCLs, for achieving arbitrary beam control, spectral emission, intensity modulation, and polarization control, so on and so forth. Photonic engineering through the design of e.g. Bragg gratings, photonic crystals, plasmonic/metasurface/metamaterial structures, and hybrid material systems, provides an excellent platform to achieve full manipulation of THz waves. In this thesis, we aim to explore photonic engineering techniques to obtain high performance THz QCLs. First, we report the design, fabrication and experimental characterization of surface-emitting THz frequency QCLs with distributed feedback concentric-circular-gratings (CCG) for beam engineering to achieve a narrow beam divergence. Single-mode operation is achieved at 3.73 THz with a side-mode suppression ratio as high as ~30 dB. The device emits ~5 times the power of a ridge laser of similar dimensions, with little degradation in the maximum operation temperature. Two lobes are observed in the far-field emission pattern, each of which has a divergence angle as narrow as ~13˚×7˚. In addition, we also report on the planar integration of tapered THz QCLs with surface plasmonic waveguides, which are developed to provide a versatile platform for beam engineering and optical components integration. For example, by introducing periodically arranged surface scatterers, the whole structure functions as an efficient collimator, resulting in a tight THz surface-emitting beam with a divergence as narrow as ~4˚×10˚. As all the structures are in-plane, this scheme also provides a promising platform for the construction of an active integrated THz photonic circuit by incorporating other optoelectronic devices such as Schottky diode THz mixers, and graphene modulators or photodectors. Furthermore, for practical applications, modulation of THz light is usually needed to encode information in THz waves or to perform lock-in amplification of the signal, etc. However, traditional THz modulators suffer from either slow modulation speed (mechanical optical chopper) or small modulation depth (electro-optical devices). Here, we demonstrate integrated THz graphene modulators on THz CCG QCLs, which enable the modulation of THz light intensity with a 100% modulation depth and a fast modulation speed.